Tantangan Rancangan Pembelajaran dalam Era Kompetensi Abad 21 untuk Meningkatkan Kemampuan Keprofesionalan dan Mengelola Pembelajaran Bermakna - Pristiwati, Rahayu (Jurnal Abdimas, 2019)
This article has purpose to improve primary teachers’ knowledge about professionalism and to manage meaningful learning about integrated lesson plan with 21st century skills, PPK, and literacy. In the implementation of Science and Technology is used two methods: training and counselling methods. The success of social devotion program by targeting primary school teachers can be seen (1) the training can improve the knowledge of the teachers about professionalism and to manage meaningful learning by designing integrated lesson plan with 21st century skills, PPK, and literacy; (2) the understanding of the teacher about professionalism and manage meaningful learning by designing integrated lesson plan with 21st century skills, PPK, and literacy which have improvement on the implementation of Science and Technology; (3) training of designing integrated lesson plan with 21st century skills, PPK, and literacy also improve professionalism and management of meaningful learning in which become the target of social devotion program in the form of Science and Technology implementations.